Le social à l'épreuve des valeurs, d'un Pays Basque à l'autre - Manterola, Jean-Jacques (PrimaLun@, 2020)
The book analyses a vast fresco at the heart of the transformations of the State, the regions and the sectors of activity, by engaging in an interdisciplinary dialogue. It contributes to the understanding of the contemporary territorial dynamics of the Social and Solidarity Economy, through two sectors of activity (integration through economic activity, home help). It shows that this territorial construction is part of a long-term process and that it obeys sectoral, cultural and institutional logics. The in-depth case studies (the two sides of the Basque Country) make it possible to give an unprecedented social and political consistency to processes that sometimes remain rather disembodied. The comparative dimension constitutes an original contribution of the work. This work certainly compares two border territories, but whose forms of institutionalisation and structuring remain relatively watertight, as far as the social sphere is concerned, under the influence of distinct welfare state systems. The comparison, deployed according to a similar methodology on both sides, forces us to discuss different models of territorialisation of public policies. The theme can be considered of major political and socio-economic importance in a context of social and economic crisis, deterioration of welfare state regimes and tightening of public policies. The detailed approach (about a hundred interviews), based on controversies on values, leads to distinguish itself from other works postulating a certain naturalization of the anchoring of the SSE in the territories, and it questions the notion of social innovation.